2011
DOI: 10.1007/s00125-011-2411-2
|View full text |Cite
|
Sign up to set email alerts
|

The course of depressive symptoms in primary care patients with type 2 diabetes: results from the Diabetes, Depression, Type D Personality Zuidoost-Brabant (DiaDDZoB) Study

Abstract: Aims/hypothesisThe aim of the study was to examine the course (incidence, recurrence/persistence) of depressive symptoms in primary care patients with type 2 diabetes and to identify significant predictors of these different course patterns.MethodsA cohort of 2,460 primary care patients with type 2 diabetes was assessed for demographic, clinical and psychological factors in 2005 and followed-up in 2007 and 2008. Depression was defined as a score of ≥12 on the Edinburgh Depression Scale. Multivariate logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 34 publications
7
65
2
3
Order By: Relevance
“…This finding is in line with results from another longitudinal study with a 3 year follow-up, examining the course (incidence, recurrence/persistence) of depressive symptoms in 2460 primary care patients with type 2 diabetes with the additional aim of identifying significant predictors of these different course patterns [13]. In this study, depression was assessed by means of a self-reported measure.…”
Section: Predictors Of Depression In Diabetessupporting
confidence: 86%
See 2 more Smart Citations
“…This finding is in line with results from another longitudinal study with a 3 year follow-up, examining the course (incidence, recurrence/persistence) of depressive symptoms in 2460 primary care patients with type 2 diabetes with the additional aim of identifying significant predictors of these different course patterns [13]. In this study, depression was assessed by means of a self-reported measure.…”
Section: Predictors Of Depression In Diabetessupporting
confidence: 86%
“…Of all participants with type 2 diabetes, 26% met the criterion for depression at one or more assessments. Incident depression at follow-up was present in 14% of individuals, whilst recurrence/persistence in those with baseline depression was found in 66% [13]. History of depression was a key clinical predictor of future depression and, once present, depression often became a recurrent condition [13].…”
Section: Predictors Of Depression In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…El 55,47% de la muestra total padecía alguna comorbilidad psiquiátrica (IC 95% BCa 50,00-61,72) y la comorbilidad médica crónica fue autoreportada en 42 …”
Section: Resultsunclassified
“…La relación bidireccional entre la depresión y la hipertensión arterial o la diabetes mellitus se encuentra bien documentada 38 , complicando el pronóstico 39,40 , implicando un mayor uso de servicios 41 , y un aumento en el riesgo de recurrencia del trastorno afectivo 42 . En Chile, los síntomas depresivos en pacientes hipertensos de APS son comunes 43 , y han sido asociados a control insatisfactorio de la presión arterial 44 .…”
Section: Discussionunclassified